2018
DOI: 10.1016/j.nut.2017.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and duration of reasons for enteral nutrition feeding interruption in a tertiary intensive care unit

Abstract: EN FI occurred primarily due to human factors, which may be minimized by adherence to an evidence-based feeding protocol as determined by a nutrition support team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 52 publications
2
27
0
7
Order By: Relevance
“…This may prompt early assessment of muscle mass for nutrition risk stratification. 33 Theoretically, appropriate nutrition and rehabilitation intervention may help to improve muscle status, and this may be translated into a survival advantage. 34 Further research is needed in this area.…”
Section: Discussionmentioning
confidence: 99%
“…This may prompt early assessment of muscle mass for nutrition risk stratification. 33 Theoretically, appropriate nutrition and rehabilitation intervention may help to improve muscle status, and this may be translated into a survival advantage. 34 Further research is needed in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Although the disease process has tremendous impact on the nutrition status of critically ill patients, depending on the patients’ history, the patients may already have features of malnutrition with a reduced or restricted food intake long before intensive care unit (ICU) admission due to the underlying chronic conditions (such as chronic obstructive pulmonary disease, cancer, or chronic renal failure) or have reduced intake from a hospital stay prior to ICU adminssion . Moreover, in the ICU, the patients may continue to have restricted nutrition intake and thus they may experience prolonged fasting or frequent feeding interruptions due to various ICU procedures . These 2 factors, preexisting malnutrition and iatrogenic underfeeding, may further complicate the nutrition status and worsen clinical outcomes.…”
Section: Pathophysiology Of Malnutrition In Critically Ill Patientsmentioning
confidence: 99%
“…6,7 Moreover, in the ICU, the patients may continue to have restricted nutrition intake and thus they may experience prolonged fasting or frequent feeding interruptions due to various ICU procedures. 8 These 2 factors, preexisting malnutrition and iatrogenic underfeeding, may further complicate the nutrition status and worsen clinical outcomes.…”
Section: Pathophysiology Of Malnutrition In Critically Ill Patientsmentioning
confidence: 99%
“…Negative nitrogen balance has been associated with increased mortality risk among critically ill patients with AKI . Additionally, studies have shown that actual nutrition support provision (particularly with enteral feedings) is often significantly less than what is prescribed by a clinician . For this reason, and the increased catabolism that is associated with critical illness and its myriad of comorbid conditions, the risk of malnutrition in the ICU is high .…”
Section: Discussionmentioning
confidence: 99%
“…The balance of providing protein in an amount that is enough to improve renal perfusion and nitrogen balance but not contribute to azotemia and exacerbate kidney insult can be a challenge for nutrition support clinicians. In addition, a common nutrition obstacle in the ICU is the fact that what is actually provided is often significantly less than what is prescribed …”
Section: Literature Reviewmentioning
confidence: 99%